MEDIA KOMUNIKASI VISUAL SEBAGAI PENUNJANG PROMOSI PADA SMK MULTIMEDIA MANDIRI - Lusyani Sunarya; Maimunah Maimunah; Ratna Sari (CCIT Journal, 2019)
Currently the visual communication media is growing very rapidly and often used as a promotional support media to convey information as effectively as possible. Visual communication media can be implemented in a school to promote and introduce the school environment to the wider community to attract the attention of prospective students who will enroll in the next academic year, such as those owned by Multimedia Mandiri Vocational Highschool. Previously the vocational highschool already has a promotional media in the form of brochures, but the brochure contained is felt less effective to promote and provide information about the school because it uses only 1 media so it attracts less attention of the public. With this research, then developed other promotion media in the form of billboards, banners, flyers, pamphlets, signboards, posters, and banners that are expected to attract public attention to Multimedia Mandiri Vocational Highschool information, increasing the number of students in the next academic year, Multimedia Mandiri Vocational Highschool can be recognized in the wider society. This research was made using data collection method, design concept, and SWOT analysis. The development of visual communication media will be made using CorelDRAW X7 application.